Human-mobility networks, country income, and labor productivity - Giorgio Fagiolo; Gianluca Santoni (Scuola Superiore Sant'Anna, Laboratory of Economics and Management (LEM), 2014)
This paper asks whether the level of integration of world countries in the international network of temporary human mobility can explain differences in their per-capita income and labor productivity. We disentangle the role played by global country centrality in the network from traditional openness measures, which only account for local, nearest-neighbor linkages through which ideas and knowledge can flow. Using 1995-2010 data, we show that global country centrality in the temporary human-mobility network enhances both per-capita income and labor productivity. Our results hold cross-sectionally, as well as in a dynamic-panel estimation, and take into account potential endogeneity issues. Our findings imply that how close a country is to the theoretical technological frontier, depends not only on how much she is open to temporary human mobility, but mostly on whether she is embedded in a web of relationships connecting her with other influential partners in the network. Our exercises also suggest that most of the gain in income and productivity can be attained if country centrality in the network comes mostly from influential partners that lie not too far away from, but neither too close to them in the network.
Keywords: O33; O47; C21; C26; F22; 330; Temporary human-mobility network; International technological diffusion; Per-capita income; Productivity; Openness to mobility and trade; Centrality